Controversies in drugs policy and practice - McKeganey, Neil P. (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
"This is a lively and provocative book on a topic of deep public and professional interest. Addressing a host of issues surrounding the place of illegal drugs in society, the text draws readers in to debates about key contemporary issues including drug treatment, harm reduction, classification, legislation and research"--Provided by publisher.
Machine generated contents note: -- The Rapidly Changing World of Illegal Drugs -- What's Wrong with Harm Reduction? -- Drug Treatment: So What's All the Fuss About? -- Drug Enforcement: A World of Myth and Reality -- Cannabis and the Classification Mystery -- Meeting the Needs of the Children of Drug Addicted Parents -- Drug Legalization: Solution or Social Problem?The Politics of Drugs Research: A Journey into the Cold -- Conclusion: So What's Morality Got to Do With It?
Keywords: Drug abuse; Drug control